2005
DOI: 10.1002/hep.20859
|View full text |Cite
|
Sign up to set email alerts
|

Altered monocyte responses to defined TLR ligands in patients with primary biliary cirrhosis

Abstract: The role of the adaptive immune response, with regard to the development of autoantibodies, has been extensively studied in primary biliary cirrhosis (PBC). However, the importance of innate immunity has been noted only recently. Based on the proposed role of microorganisms in the pathogenesis of the disease, we hypothesize that patients with PBC possess a hyper-responsive innate immune system to pathogen-associated stimuli that may facilitate the loss of tolerance. To address this issue, we isolated periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 35 publications
7
128
0
2
Order By: Relevance
“…TLR4 expression is significantly elevated in biliary epithelial cells and periportal hepatocytes of PBC patients [62]. Monocytes from PBC patients appear more sensitive to the ligand for TLR4 (LPS), producing higher levels of proinflammatory cytokines, particularly IL-1b, IL-6, IL-8, and TNF-a [63].…”
Section: Hepatic Autoimmune Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR4 expression is significantly elevated in biliary epithelial cells and periportal hepatocytes of PBC patients [62]. Monocytes from PBC patients appear more sensitive to the ligand for TLR4 (LPS), producing higher levels of proinflammatory cytokines, particularly IL-1b, IL-6, IL-8, and TNF-a [63].…”
Section: Hepatic Autoimmune Disordersmentioning
confidence: 99%
“…Data regarding expression of TLR4 in cirrhotic patients are conflicting, with studies showing increased expression on BEC, maintained or increased expression on hepatocytes, and maintained or decreased expression on PBMC [62][63][64][69][70][71].…”
Section: Hepatic Fibrosismentioning
confidence: 99%
“…It was shown that patients with PBC have higher levels of TLR3, TLR4 and TLR9 receptors in the liver [103,104] . In vitro stimulation of monocytes from PBC patients with several TLRbinding molecules resulted in higher levels of cytokine secretion [105] . PBMCs from PBC patients, when cultivated www.wjgnet.com …”
Section: Modulation Of Gene Expression: the Role Of The Innate Immunementioning
confidence: 99%
“…This finding was specific for the disease and correlated with more florid histological lesions. Moreover, Mao et al reported that PBC patients were hyper-responsive to LPS stimulation, and suggested that aberrant signaling through TLR4 may precipitate disease onset [32]. Therefore, it has been hypothesized that TLR4 and its ligands would be implicated in the development of PBC, but the results of our SNP analysis indicated otherwise.…”
Section: Discussionmentioning
confidence: 66%